Conversion Paralysis After Cervical Surgery: A Case Report and Literature Review - Fang, Miao; Zhou, Jiaojiao; Zeng, Yong; Huang, Shishu; Song, Yueming (Frontiers in Surgery, 2022)
We report a case of conversion paralysis triggered by cervical surgery that was caused by cervical spondylotic myelopathy (CSM). A 67-year-old man underwent anterior cervical corpectomy decompression and fusion for CSM. Upon awakening from the anesthesia, he had incomplete paraplegia. Emergency surgery for hematoma evacuation was performed, but no obvious hematoma was found. After the second surgical procedure, he showed paraplegic. When the patient was informed that a third operation was needed, he recovered almost completely without any treatment. This case reminds us that spine surgeons should be aware of possible conversion paralysis, especially in patients who develop a new neurological deficit after spinal surgery.